2013
DOI: 10.1080/00150193.2013.842105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodispersed Perovskite Barium Zirconate (BaZrO3) by the Sonochemical Method

Abstract: Barium zirconate (BaZrO 3 ) was synthesized successfully by the sonochemical method. The monophase of BaZrO 3 was formed completely in short irradiation time without the calcination process. X-ray diffraction, Fourier transform and Raman spectroscopy were used to characterize formation of the perovskite BaZrO 3 phase, which occurs in a 60 minute single phase with a cubic crystal structure at room temperature. Therefore, sonochemical irradiation could accelerate the formation of BaZrO 3 particles significantly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The process of crystalline BYZ formation observed in this study is similar to that reported by Charoonsuk et al . for preparing barium zirconate (BaZrO 3 ) by the sonochemical method …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of crystalline BYZ formation observed in this study is similar to that reported by Charoonsuk et al . for preparing barium zirconate (BaZrO 3 ) by the sonochemical method …”
Section: Resultsmentioning
confidence: 99%
“…The process of crystalline BYZ formation observed in this study is similar to that reported by Charoonsuk et al for preparing barium zirconate (BaZrO 3 ) by the sonochemical method. 37 The phase composition of the powders prepared by the sonochemical method at different ultrasonication times was further studied by FT-IR and Raman spectroscopy. The IR spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the concentration of solution drops to an equilibrium concentration, which enters the growth process [33]. Thus, synthesis of BaZrO 3 by the sonochemical method in ethanol/water mixed solvent clearly takes a shorter irradiation time than synthesis in aqueous solution [19]. In addition, the relative content of ethanol and boiling point of solvent are other possible reasons for BaZrO 3 phase formation, as the boiling point of ethanol (78.3 1C) is lower than that for water (100 1C) [34], and so the boiling point decreases with increasing percentage by volume of ethanol.…”
Section: Characterizationmentioning
confidence: 99%
“…The pure perovskite BaZrO 3 phase was seen clearly at 60 min irradiation time [19]. For the first time, this work attempted to find the effect of ethanol content in ethanol/water mixed solvents on the synthesis of perovskite BaZrO 3 product powders by changing the percentage of ethanol volume.…”
Section: Introductionmentioning
confidence: 99%
“…19,30 Most of the extra steps can introduce a serious problem if any contamination or loss of Ba:Zr ratio occurs. 30 Among the solution methods developed so far, recent publications from these authors also proposed sonochemical 31,32 and soft-mechanochemical methods, 33 in which calcination or heat treatment was unnecessary. It seems that smart techniques fulfill the characteristic requirements for synthesizing the extreme nm-BaZrO 3 fine powders.…”
mentioning
confidence: 99%